2019
DOI: 10.1152/ajpregu.00298.2018
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory reflex action of splanchnic sympathetic nerves is distributed across abdominal organs

Abstract: The splanchnic anti-inflammatory pathway has been proposed as the efferent arm of the inflammatory reflex. Although much evidence points to the spleen as the principal target organ where sympathetic nerves inhibit immune function, a systematic study to locate the target organ(s) of the splanchnic anti-inflammatory pathway has not yet been made. In anesthetized rats made endotoxemic with lipopolysaccharide (LPS, 60 µg/kg iv), plasma levels of tumor necrosis factor-α (TNF-α) were measured in animals with cut (Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 38 publications
4
25
0
Order By: Relevance
“…Concerning the heart rate, we observed that all doses tested increased this hemodynamic parameter, over time, supporting previous observation (Altavilla et al, 2002). Moreover, in agreement with previous studies (Martelli et al, 2019), our findings demonstrated that the lowest dose tested (0.06 mg/kg) reduces the mean arterial pressure over time. However, it has been described a transient increase in mean arterial pressure, 2 and 3 h after LPS administration, with the return of this hemodynamic parameter to baseline, 4–6 h later, using the same dose (0.06 mg/kg) (Martelli et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Concerning the heart rate, we observed that all doses tested increased this hemodynamic parameter, over time, supporting previous observation (Altavilla et al, 2002). Moreover, in agreement with previous studies (Martelli et al, 2019), our findings demonstrated that the lowest dose tested (0.06 mg/kg) reduces the mean arterial pressure over time. However, it has been described a transient increase in mean arterial pressure, 2 and 3 h after LPS administration, with the return of this hemodynamic parameter to baseline, 4–6 h later, using the same dose (0.06 mg/kg) (Martelli et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…However, it has been described a transient increase in mean arterial pressure, 2 and 3 h after LPS administration, with the return of this hemodynamic parameter to baseline, 4–6 h later, using the same dose (0.06 mg/kg) (Martelli et al, 2014). Apropos, this dose of LPS has been extensively used in rats for investigating the mechanisms involved in the inflammatory reflex pathway (Martelli et al, 2014, 2019; Komegae et al, 2018), as well as for evaluating the baroreflex regulation during systemic inflammation (Tohyama et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated in rats that the splanchnic nerve-mediated anti-inflammatory action is distributed across the abdominal organs innervated by that sympathetic nerve, including the spleen, intestines, stomach, pancreas, liver and adrenal medulla 16 . While the splanchnic nerves drive the release of catecholamines from the adrenal medulla 17 , the reflex survives adrenalectomy, indicating that direct release of neurotransmitters from sympathetic nerve terminals suppresses inflammation 16 . We infer that removal of the braking influence of the splanchnic nerves enhances the capacity to sequester and kill circulating bacteria by phagocytic and cytotoxic cells distributed broadly in the abdominal viscera.…”
Section: Discussionmentioning
confidence: 99%
“…It was already demonstrated that septic patients show a loss of sympathetic splenic nerves, indicating a regulating role in disease [77]. Nevertheless, recent insights also show that the spleen might not be as essential as previously believed, since the anti-inflammatory properties of splanchnic nerve stimulation are spread across other abdominal organs such as the liver and adrenal glands [78].…”
Section: Importance Of the Spleen In Mediating The Caipmentioning
confidence: 99%